Indonesia International Trade Facing AEC in Islamic Economic Perspektive - Sri Herianingrum (Universitas Bina Darma, 2015)
Currently Indonesia international trade is facing to experience challenges the presence of AEC in force in 2015.In the approach to free trade, Indonesia's foreign trade can be analyzed with a regional approach or customs unions. In addition, Krugman and Obstfeld reveal differences in free trade and customs unions. The difference in the concept c Islamic trade including international trade Islam with the concept of international trade and Obsfeld Krugman is the spirit that underlies the concept of Islam based monotheisme while the conventional concept based on sheer material. Methods of this study used a qualitative approach with methods of literary study The information extracted is literature on Indonesia international trade in Islamic Economic perspective. The results of the literature is Indonesia needs to seriously improve the quality and quantity of good products intended for export and to meet domestic consumption. In connection with the Indonesian economy is still dominated by the conventional concept that liberalism, capitalism, then to its current state is very necessary to implement review, and consider the contents of international trade agreements both regional and international, in an effort to protect producers, consumers in the country, as well as maintain the resilience of nations in all aspects of life.